POSSIBILITIES OF USING CRYOSURGICAL METHOD IN TREATMENT OF DEPTH BRAIN TUMORS - A. I. Kholyavin; V. B. Nizkovolos; B. V. Martynov; D. V. Svistov; A. D. Anichkov; N. P. Alekseeva (Вестник хирургии имени И.И. Грекова)
Cryosurgical method is used in treatment of patients with glial tumors which localized in depth and functionally meaningful brain areas. These patients are generally considered as inoperable and receive conservative treatment. Their prognosis has become worse as compared to the patients whose brain tumor is available for surgical removal. The authors used a multiway stereotactic destruction of tumors by cryosurgical cannula, which is inserted in bone cutter opening using manipulator. MR-imaging and PET/CT of brain were applied for stereotactic guidance. The majority of patients who underwent this operation didn’t noticed any loss of quality of life. The rates of survival were higher than corresponding indicators for patients who were treated only by chemo- or radiation therapy and the rates were equal to the patients underwent the radical operations. Thus, the multiway stereotactic cryodestruction is a new, safe and effective method of surgical treatment for the patients with tumor localization in such areas, that their location blocked an application of traditional surgical removal by open method.